Testimony and Identity in Burma - Alison Francis (Journal of Southeast Asian Human Rights, 2021)
The oppressive force of the Burmese military continues to inflict abuse upon the many different ethnic groups within its borders. Women have been at the forefront of resistance using testimony, using the medium to resist the oppression of the state military through language. This article examines the testimonial as a site of resistance through a dialogical analysis of two texts representative of historical moments in Burma’s history of state oppression. It argues that the language of testimony creates spaces for identity formation as a form of resistance. Through a dialogical analysis of two testimonies representative of different political moments, this article builds upon this notion, and argues that the testimonial not only represents a site of resistance and space of identity formation for women oppressed within the bounds of the state, but also allows for the reassertion of collective identities that stand as a foundation for collective action.